2020
DOI: 10.1093/mnras/staa430
|View full text |Cite
|
Sign up to set email alerts
|

The three causes of low-mass assembly bias

Abstract: We present a detailed analysis of the physical processes that cause halo assembly bias -the dependence of halo clustering on proxies of halo formation time. We focus on the origin of assembly bias in the mass range corresponding to the hosts of typical galaxies and use halo concentration as our chief proxy of halo formation time. We also repeat our key analyses across a broad range of halo masses and for alternative formation time definitions. We show that splashback subhaloes are responsible for two thirds of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 101 publications
(211 reference statements)
3
46
1
Order By: Relevance
“…Our measurements of 𝑐 200c for the low halo mass end -where halos are more poorly resolved, and can sometimes have density profiles that vary significantly from NFW -show a handful of halos have very high concentrations, up to 𝑐 200c ∼ 300, and this is also found in several recent works (e.g., Diemer & Kravtsov 2015;Mansfield & Kravtsov 2020). Here, we employ a simple 3𝜎 filtering procedure across the whole halo sample in order to remove any such outliers from our analysis.…”
Section: Concentration 𝑐 200csupporting
confidence: 85%
See 1 more Smart Citation
“…Our measurements of 𝑐 200c for the low halo mass end -where halos are more poorly resolved, and can sometimes have density profiles that vary significantly from NFW -show a handful of halos have very high concentrations, up to 𝑐 200c ∼ 300, and this is also found in several recent works (e.g., Diemer & Kravtsov 2015;Mansfield & Kravtsov 2020). Here, we employ a simple 3𝜎 filtering procedure across the whole halo sample in order to remove any such outliers from our analysis.…”
Section: Concentration 𝑐 200csupporting
confidence: 85%
“…The scatter also has a significant, mass-dependent increase below 𝑀 200c < 10 11 M , caused by the tail to high 𝑐 200c . This tail is almost entirely accounted for by low-mass halos that reside near more massive halos and have had their DM phase-space altered via strong tidal interactions with these massive neighbors (see Figure 6 in Mansfield & Kravtsov 2020). We have confirmed that removing such halos subdues the increase in the scatter at low masses seen in 𝑐 200c and in 𝜎 DM, 3D .…”
Section: Nfw Concentration 𝑐 200csupporting
confidence: 58%
“…It is well known that haloes of a fixed mass bin exhibit different clustering properties depending on whether they are sub-selected on certain properties. This effect, originally discovered in the context of assembly history, and generally known as assembly bias or secondary bias, has been observed for selections on concentration, occupation, local environment, spin, and other secondary halo properties (Wechsler et al 2002;Gao et al 2005;Wechsler et al 2006;Dalal et al 2008;Mao et al 2018;Salcedo et al 2018;Mansfield & Kravtsov 2020).…”
Section: Fitting Assembly Bias and Baryonsmentioning
confidence: 94%
“…While previous work has focused on evolution of exquisitely resolved cores, evaporation of subhalos, or mergers of massive clusters [35][36][37][38][39][40][41][42], in this paper we focus on large cosmological boxes to look at statistical samples of cluster mass halos and their subhalos that cover the comprehensive range of histories and environments in the universe. Recently, a feature in the outskirts of the density profile of halos, the splashback radius [43][44][45][46], has emerged as a probe for physics at the interface of galaxy formation [47][48][49] and cosmology [47,50]. [51,52].…”
Section: Introductionmentioning
confidence: 99%